RANCANG BANGUN SISTEM INFORMASI NOTULENSI MENGGUNAKAN FRAMEWORK CODEIGNITER DAN DATABASE MYSQL DI UNIVERSITAS KATOLIK WIDYA KARYA MALANG - Yohaness Beatrixs Yonkman Oybur; Michael Gerits Kriswanto Remetwa; Winarto Eko Wahyono (Universitas Katolik Widya Karya Malang, 2023)
Documentation in the digital era is a trend that is used daily both in the form of lecture material documents, scientific literature such as journals, ebooks and so on. Ease of access, conciseness, and saving paper characterizes digital documents, as well as documentation of activities, both photos and minutes of meetings. The problem raised in this study is that meeting and seminar activities at Widya Karya Catholic University in Malang have not been properly recorded, this is because the recording of minutes is done manually and is not stored centrally, making it difficult at times, for example accreditation to access the results of meeting discussions, therefore the authors designed and built a website-based note-taking system so that it can be easily accessed. System development using the php codeigniter framework and mysql database results in a centralized note taking system that is easy for users to use.